Meningkatkan Daya Saing UMKM Lampung melalui Pelatihan Manajemen Keuangan Syariah dan Pendampingan Legalitas Usaha - Joni Putra; Aryan Danil Mirza. BR; Neny Desriani; Rindy Dwi Ladista (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
MSMEs are a strategic sector in the Indonesian economy. However, many MSMEs face fundamental obstacles in the form of low business legality and minimal Islamic financial literacy, requiring comprehensive assistance. This community service activity aims to improve the competitiveness of MSMEs through business legality assistance based on Online Single Submission (OSS) and Islamic financial management training. This PKM involves 12 MSMEs from various sectors, including food and beverage, makeup services, Pahawang tour services, and local honey production. The training was held on September 5, 2025, at Maharindu Kopi, Bandar Lampung. Participants received educational materials, hands-on practice in registering for a Business Identification Number (NIB), and training in Islamic financial literacy. The results of the activity showed that 10 of the 12 MSMEs successfully obtained business legality in the form of an NIB. In addition, the participants' Islamic financial literacy increased significantly, with an average increase in understanding of 40-50% after participating in the training. Participants also began to be able to prepare simple sharia-based cash flow reports and recognize sharia financial products relevant to their businesses. The success of this program has great potential to be expanded to other regions as a model for empowering competitive, professional, and sustainable MSMEs.